Efeito da umidade na rigidez da madeira de Pinus elliottii e Bertholletia excelsa Humn. &. Bonpl. - Ferreira, Pâmela da Silva (2020)
Non-destructive methods have been successfully applied in estimating the wood properties due to its speed, in relation to classic methods, and, above all, by allowing the same specimen to be reused. In addition, the mechanical properties of wood are strongly influenced by moisture and density, but little is known about the effect of density on the moisture x stiffness in wood. The aim of this study was to evaluate the influence of moisture on the dynamic elastic modulus (DEM) and the wave propagation speed (WSP) of stress waves in low and high basic density wood, as well as to verify the effect of apparent density on the relationship stiffness x moisture in the wood. The log from the base of Pinus elliottii and Bertholletia excelsa trees from experimental plantings was processed to remove prismatic specimens in the dimensions of 410 mm in the longitudinal axis and 25 mm of edge in the square cross section oriented according to the growth rings. The estimation of DEM and WSP was obtained from the method of transverse vibration from 30 wood samples from Pinus and 40 from Bertholletia. The sound resonance analyses were performed on the specimens at equilibrium moisture, after saturation in water, during water desorption to anhydrous condition and during water adsorption until equilibrium humidity was reached again. The reduction in moisture provided an increase in the modulus of elasticity and the speed of propagation. At equilibrium moisture of 12%, Pinus obtained an MOE of 11,41 GPa and Bertholletia of 14,96 GPa, as well as in the other water contents, the species with the highest density showed the highest MOE and VP. The apparent density showed a strong correlation with the modulus of elasticity for both 12% and 90% moisture. However, it was not possible to observe density interference in the wood's hygromechanical behavior. Flexural strength showed a similar variation for both species.